ПРЕДПОСЫЛКИ И УСЛОВИЯ ФОРМИРОВАНИЯ МОДЕЛИ«ТРОЙНОЙ СПИРАЛИ» ИННОВАЦИЙ В КАЗАХСТАНЕ - F. M. Dnishev; A. S. Gabdulina (Экономика: стратегия и практика)
The purpose of the paper is to consider the concept of the “triple helix of innovations”, to study the preconditions of it’s formation and to identify the conditions for the implementation of the “triple helix of innovations” model into the innovative practice of Kazakhstan.The research methodology in the paper is based on ideas about the evolution of innovation and innovation systems, the multiple nature of models of innovation systems based on the specifics of the institutional environment.It is shown that the development of innovative systems in the world is based on strong horizontal interactions between science, business and government which have an equal partnership among them as a “triple helix”. However, the key conditions and assumptions of the “triple helix” model do not work in Kazakhstan and the existing relationship between science, business and government does not allow to rely on establishing the principles of “a triple helix” of innovations in the national scale.It is proposed to develop local innovation systems in Kazakhstan according to the “triple helix” model. The preconditions for the formation of local “triple helix” model on the basis of research universities and technoparks are observed, and the conditions for their development are formulated.